Environmental Factors that are at Risk of Heat Stress Exposure to Fishermen in Indonesia - Putri Ayuni Alayyannur; Doni Hikmat Ramdhan; Mila Tejamaya (Universitas Airlangga, 2023)
Introduction: Workers face pressure that comes from the work environment, one of which is heat pressure. Exposure to heat, workload, rehydration, and rest period are several factors that can cause heat stress to workers. People who are uncovered to heat are much more likely to experience heat stress. Related to this, current research was carried out aiming to analyze environmental factors that are at risk of heat stress exposure to fishermen in Indonesia. Methods: This study was conducted through a cross sectional design in the coastal regions in Surabaya. Accidental sampling technique was applied, obtaining 42 respondents. In this case, the variables included are humidity, temperature, access to clean water, risk of heat stress, and dehydration, while the data analysis techniques used are the logistic regression and pearson correlation. Results: The results showed that the significant environmental factor is access to clean water, with a value of 0.009 so that the p-value is less than 0.05. Furthermore, the relationship between heat stress and dehydration is 27.1%. Conclusion: Therefore, this study concludes that only access to clean water is significantly related to the risk of heat stress. In addition, the relationship between heat stress and the incidence of dehydration is weak.